(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses the synthesis of a complex compound containing [Ni(Sal)2(H2O)4] (Sal-salicylamide) and its crystal structure. The synthesized complex compound was studied by IR-Fourier spectroscopy, elemental analysis and X-ray structural analysis method. It was shown by X-ray structural analysis (RTT) method that nickel is coordinated with the selected ligand salicylamide through the oxygen atom of the carbonyl group, and that the hydroxyl group does not participate in the coordination. The stimulatory properties of the complex obtained by the reaction of Ni(II) ion with salicylamide were investigated and it was determined as a result of experiments that it increased compared to the initial ligand. This stimulator was applied to rice plants growing in saline soil in Khorezm region, and positive results were obtained. The surface analysis of the complex compound was carried out using the Crystal Explorer 17.5 program, and it was proved that intermolecular hydrogen bonds make a significant contribution (23.3%) to the structure of the compound in the crystalline state.